AN ANALYSIS OF CODE-SWITCHING IN ENGLISH MEETING CLUB (Benteng Panynyua Club in Fort Rotterdam Makassar) - Juvrianto CJ (ETERNAL (English, Teaching, Learning and Research Journal), 2018)
Code-Switching is a phenomenon that may occurs in Bilingual or Multilingual communities. Indonesian students who learn English as Foreign Language tend to find a way to master English by forming or joining an English Meeting Club. Code -Switching occurs when they try to speak English in their conversation. The aim of this study is to describe the type of Code-switching used by the members of English meeting club and reason why they did that switching. This research used qualitative method. The subject of the research was participants of English Meeting Club and the data of Code-switching are taken from recording which was converted into transcription.  The result shows that the members of English meeting club did three types of Code-switching. Those are tag-switching, intra-sentential switching and inter-sentential switching. They mostly used intra-sentential switching in their conversation and did the switching to make their utterances acceptable to the hearer.